(3GdeSQM GdeZQHj (B:s (3Hjf GSFdI GdcJGHI GdGHOGYjI h GdeeGQSI GdfbOjI (B/s - (3aQGM,eMeO s ((3GdOGQ GdHjVGA (B:s (3OGQ GdKbGaI ,s, 2000)
(3GdeSQM GdYQHj h eSCdI GdfbO(B,(3GdeSQM GdeZQHj h GdeeGQSI GdfbOjI(B,(3echfGJ GdNWGH GdfbOj GdeSQMj HGdeZQH(B.s
Keywords: (3GdcJGHI GdGHOGYjIs; (3GdeSQMs; (3GdeeGQSI GdfbOjI s